PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA PEREMPUAN DI BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU AHMAD YANI PEKANBARU - Putri Maharany Ayu Hasibuan; Maria Maya Lestari; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Protection of labor is a form of government interference in the field oflabor aimed at realizing a fair labor. The Manpower Law became a legalumbrella for the protection of labor, even more so for female labor. Consideringthat there is a uniqueness possessed by women both in terms of physical, psychic,and biological, so that more special protection is given. Special protections areprovided to the female workforce such as menstrual leave, maternity andmaternity leave, and the right to breastfeed children. Legal protection of women'slabor rights becomes an obligation for employers to do so. But in itsimplementation, the legal protection that should be provided by entrepreneurs isstill not carried out perfectly, due to the presence of several obstacles forentrepreneurs. In this thesis, the researcher tried to examine how theimplementation of legal protection for female workers at Bank Syariah IndonesiaKCP Ahmad Yani Pekanbaru and addressed what obstacles the companyexperienced to provide full legal protection. The purpose of writing this thesis isto find out how the implementation of the provision of legal protection for femaleworkers funds pa obstacles faced by companies to carry it out.The research method used in this thesis is the sociological legal researchmethod. This research is descriptive, that is, it defines and describessystematically, the facts and characteristics of objects that are preciselycontextualized. The data sources used are primary, secondary, and tertiary datasources. The data collection technique used in the study in this study was to usethe interview method and literature study.Based on the results of the study, there are special rights of women's laborthat have not been fully realized by the company, where there are obstaclesstemming from internal company factors in providing legal protection guaranteesfor female workers.Keywords : Legal Protection, Women's Labor Rights, Company Obligations